A Green Approach to Valorizing Abundant Aquatic Weeds for Nutrient-Rich Edible Paper Sheets Production in Bangladesh - Sharmin Suraiya; Suraiya Afrin Bristy; Md. Sadek Ali; Anusree Biswas; Md. Rasal Ali; Monjurul Haq (Clean Technologies, 2023)
The rapid and unprecedented expansion of the global population highlights concerns about the sufficiency of food resources to sustain this growth. This study investigates and substantiates the feasibility of renewable food resources in order to meet the nutritional requirements of consumers. Three edible aquatic weeds, helencha (Enhydra fluctuans), malancha (Alternanthera philoxeroides), and kalmi (Ipomoea aquatica), were used to produce edible paper sheets. The composition of the raw aquatic weeds and paper sheet samples was analyzed, including the proximate composition, amino acid content, minerals and heavy metal contents, and bioactive compounds. The dried raw aquatic weeds and paper sheets showed similar proximate compositions, with carbohydrates being the highest component (50.38–64.63%), followed by crude protein (15.25–19.13%), ash (9.30–15.88%), and lipid (1.55–3.43%). The raw weeds and paper sheets were rich in essential minerals like Na, Ca, and Zn with contents ranging from 27.7 mg/100 g to 30.4 mg/100 g, 126.8 mg/100 g to 489.65 mg/100 g, and 4.5 mg/100 g to 16.3 mg/100 g, respectively. Acceptable levels of heavy metals, including Ni, Pb, and Cu, were found. The paper sheets contained seven essential and eight non-essential amino acids. Among the essential amino acids, the phenylalanine content was the highest at 2735.9 mg/100 g in E. fluctuans paper sheets, followed by methionine at 2377.29 mg/100 g in the raw E. fluctuans and histidine at 1972.6 mg/100 g in E. fluctuans paper sheets. A. philoxeroides sheets showed the highest total amino acid content (16,146.81 mg/100 g), while I. aquatica showed the lowest (13,118.67 mg/100 g). The aquatic weed paper sheets were rich in bioactive compounds, and the numbers in E. fluctuans, A. philoxeroides, and I. aquatica paper sheets were 31, 33, and 40, respectively. There were no significant changes in the nutritional content of the aquatic weeds in paper sheet form compared with the raw weeds, which suggests promising prospects for their production and consumption as a source of nutrition and bioactive compounds.